Seasonal changes in whole body and regional body composition profiles of elite collegiate ice-hockey players - Prokop, N. W.; Reid, R. E. R.; Andersen, R. E. (The Journal of Strength and Conditioning Research, 2016)
The monitoring of a collegiate hockey player's body composition can reflect fitness characteristics and may help players, coaches, or strength and conditioning specialists optimize physiologic gains during an off-season, whereas simultaneously preventing performance decrements in-season. The purpose of the study was to investigate changes in whole-body and regional-body composition of fat and lean tissue. The body composition profiles of 19 elite Canadian collegiate hockey players were assessed using dual energy X-ray absorptiometry. Players completed end-of-season, preseason, and midseason assessments with questionnaires relating to their off-season and in-season training. Statistically significant changes in body composition profiles were observed between the different time points because players showed various tissue gains and losses depending on the region assessed. Overall, players gained (1.38 kg, p = 0.01) and lost (0.79 kg, p = 0.01) fat tissue during the off-season and in-season, respectively. Players also showed a significant gain of leg lean tissue (0.29 kg, p = 0.02) and loss of arm tissue mass (-0.25 kg, p = 0.02) during the first-half of the competitive season. Several correlations emerged that may provide insight into potential trends that could be more pronounced during longer and more demanding schedules. Collegiate hockey players show changes in body composition during the off-season and in-season. The understanding of body composition profiles, body composition fluctuations, and potential variables that may influence the composition of collegiate hockey players can help coaches and athletic programs tailor their team's training, nutrition, lifestyle, and informative resources to further support their athletes.